“Seis tetas” by Camila Sosa Villada: eco-poetics of queer existence - Morais de Souza, Ana Carolina (2026)
Contemporary Latin American literature includes among its highlights the Argentine writer Camila Sosa Villada, who has become famous for addressing the complex and magical existence of the travesti body in society. The short story “Seis Tetas,” included in the anthology Soy una tonta por quererte (2022), approaches this theme from a more specific perspective: that the queer body has its own nature and represents unimaginable possibilities. In this way, the aim of this work is to analyze how short story “Seis tetas” constructs a narrative in which travestiness is configured as a post-natural ontological regime that articulates contamination, monstrosity, and abjection in order to destabilize the boundaries between the human, the animal, and the environmental. After carrying out a reading that sought to identify the eco-poetics of queer existence in that short story, we found that Sosa Villada’s literary expression does not seek recognition or to serve as an answer, but rather takes shape as resistance. Therefore, we conclude that her proposal is to bring the dissident body to the forefront, granting it the prominence it has historically been denied.